Model Multi Objektif untuk Pemilihan Supplier Industri CPO pada Jaringan Rantai Pasokan Ramah Lingkungan dengan Ketidakpastian Pasokan - Habibi, Rizki; Panjaitan, Arie Candra (Indo-MathEdu Intellectuals Journal, 2024)
This study proposes a mathematical model for the problem of selecting suppliers for the palm oil industry by considering the green factor. Stochastic parameters are also considered to deal with uncertain parameters in green supply chain networks. The objective of this model is to select suppliers considering the total costs and total greenhouse gas emissions. This paper aims to present a more comprehensive model based on real-world conditions for the supplier selection problem of green supply chain in the palm oil industries under uncertainty. Besides economic issues, environmental issues are also considered from several aspects such as selecting environmentally friendly suppliers and purchasing from them and considering the environmental impact of the finished product. The results show that increasing one of the indicators such as the number of products and market demand leads to an increase in the value of the total objective function, which is caused by an increase in problem size. On the other hand, the cost function increases when most supplier selection is environmentally friendly suppliers. Meanwhile, the function of the objective level of greenhouse gas emissions increases when the selection of suppliers is most suppliers with high greenhouse gas emissions, but the objective function of costs decreases